Manhaj Al-Tarbiyyah Al-Imaniyyah Lit Tifl Al-Mustanbhat Min Kitâb Tuhfathul Maudud Bi Ahkâmil Maulud Wa Kitab Tarbiyatul Aulâd Fil Islâm - Muhammad Khanif (Rayah Al-Islam, 2020)
This research aims to unveil the method of faith education for the chil and clarify it with everyone on his shoulders the responsibility of raising the child on faith until it becomes clear to each of the parents a correct approach to be taken in raising their children on faith, this approach is drawn from the two books, they are thuhfatul maudud bi ahkamil maulud by imam allama the educator Ibn Qayyim Al- Jawzia, and the book tarbiyatul aulad fil islam by contemporary educator Sheikh Abdullah Nasih Alwan. The research focuses on devising an integrated educational curriculum from the faith side, which was deduced from the prophetich curriculum based on the evidence of transmission from the Qur’an and Sunnah. Faith education begins with the child before he is born, upon his birth, and after his birth.